Village Baseline Study: Site Analysis Report for Usambara – Lushoto, Tanzania (TZ0105) - Onyango, Leah; Mango, Joash; Kurui, Zena; Wamubeyi, B.; Basisi H; Musoka E; Sayula, George (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
The village baseline study of Kwang’wenda village in the CCAFS benchmark Lushoto site, Tanzania took place from April 27 to 29, 2011. Focus group discussions were conducted separately for men and women. Population growth and agriculture intensification have led to encroachment onto the forest areas, reduction in riparian vegetation, cultivation along the riverbank, and soil fertility depletion on the farmland. The overall area under farming has increased but individual farms have become smaller and production per unit area has reduced due to land subdivision. The community’s vision of the future includes the conservation and expansion of the forest area by planting more trees and enforcing restrictions on illegal logging. It also calls for promoting agroforestry systems in the farmlands and allowing riverine vegetation to mature, in order to ensure clean waters in the rivers. The discussion groups identified 32 organisations, and 60% of them were involved in food security assistance, prioritizing food availability. Radio is the most significant source of information on agriculture in the village. Men were better informed about and interacted with groups that operated beyond the locality, while women were more aware of and engaged in groups that operated within the community but had limited operational capacity.